Identification of a novel type II-C Cas9 from the fish pathogen Flavobacterium psychrophilum - Chen, Fuguang; Wang, Di; Lu, Tongyan; Li, Shaowu (Frontiers in Microbiology, 2023)
Flavobacterium psychrophilum is the causative agent of rainbow trout fry syndrome and bacterial cold-water disease in salmonid fish worldwide. As an important fish pathogen, F. psychrophilum is frequently exposed to multiple invading genetic elements in natural environments. Endonuclease Cas9 provides bacteria with adaptive interference against invading genetic elements. Previous studies revealed that several F. psychrophilum strains harbored a type II-C Cas9 called Fp1Cas9, but little is known about the potential role of this endonuclease against invading genetic elements. In this work, we identified a gene encoding a novel type II-C Cas9 called Fp2Cas9 from F. psychrophilum strain CN46. Through bacterial RNA sequencing, we demonstrated active transcription of both Fp2Cas9 and pre-crRNAs in strain CN46. Bioinformatics analysis further revealed that the transcription of Fp2Cas9 and pre-crRNAs was drove by a newly integrated promoter sequence and a promoter element embedded within each CRISPR repeat, respectively. To formally demonstrate that Fp2Cas9 and associated crRNAs yielded functional interference in strain CN46, a plasmid interference assay was performed, resulting in adaptive immunity to target DNA sequences in Flavobacterium bacteriophages. Phylogenetic analysis demonstrated that Fp2Cas9 was present only in several F. psychrophilum isolates. Phylogenetic analysis revealed that this novel endonuclease was probably acquired through horizontal gene transfer from the CRISPR-Cas9 system in an unidentified Flavobacterium species. Comparative genomics analysis further showed that the Fp2Cas9 was integrated into the type II-C CRISPR-Cas locus in strain CN38 instead of the original Fp1Cas9. Taken together, our results shed light on the origin and evolution of Fp2Cas9 gene and demonstrated that this novel endonuclease provided adaptive interference against bacteriophage infections.